Possibility of drug-free correction of biliary system disorders in employable patients with chronic stress and neurosis - O. A. Poddubnaya; O. I. Ugolnikova; T. Ye. Levitskaya; I. G. Skurlatova; I. Yu. Lyapunova (Бюллетень сибирской медицины)
In the clinical practice, an increase in the efficiency of combined treatment of employable patients with biliary system diseases working under adverse conditions and having chronic stress and neurosis is very urgent. The use of drug-free treatment including antistress measures is justified. Tentative results are indicative of the positive effect of this approach on the functionnal state of biliary system organs with reduction of neurosis and state anxiety and with increase in the index of psychological weightness.